2017
DOI: 10.1002/chem.201701722
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of Bifunctional WS3−x/Reduced Graphene Oxide Hybrid for Hydrogen Evolution Reaction and Oxygen Reduction Reaction Electrocatalysis

Abstract: A multitude of research into the application of transition-metal dichalcogenides as earth-abundant hydrogen evolution reaction (HER) electrocatalysts has been conducted. However, current synthetic methods generally deploy environmentally harmful chemicals and energy-consuming reaction conditions, despite the primary intent to attain renewable energy production. Here, the desirable properties of tungsten sulfide and reduced graphene oxide (rGO) have been combined and hybrid materials have been fabricated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 73 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Groups of transition metal compounds that have electrochemical activity for HER and OER are often effective in the ORR reaction in many cases . Transition metal oxides are frequently used in ORR reactions with the help of rGO despite the disadvantages of their low conductivity and deficient active sites.…”
Section: Electrochemical O2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups of transition metal compounds that have electrochemical activity for HER and OER are often effective in the ORR reaction in many cases . Transition metal oxides are frequently used in ORR reactions with the help of rGO despite the disadvantages of their low conductivity and deficient active sites.…”
Section: Electrochemical O2 Reductionmentioning
confidence: 99%
“…Transition metal sulfides, the attractive materials especially for water splitting, are also effective to ORR when combined with rGO . Gautam et al reported that a FeS anchored rGO hybrid nanocomposites exhibited a remarkably improved catalytic performance for ORR.…”
Section: Electrochemical O2 Reductionmentioning
confidence: 99%
“…The novel electrocatalysts showed enhanced performance for ORR, due to their strong interaction between MoS 2 and carbon layer, high conductivity, and high specific surface area. Recently, it has been reported that Ni 3 S 2 [36] and WS 3−x [37] are also potential catalyst for ORR. Furthermore, metallic double sulfides as an ORR catalyst were investigated in recent years.…”
Section: Metal Chalcogenide-based Active Sitesmentioning
confidence: 99%
“…Among these anode materials, metal sulfides as anode materials are one kind of promising candidates due to the high specific capacities, and molybdenum based sulfides have been widely investigated for both LIBs and SIBs owing to their peculiar structure merits . Besides layered MoS 2 , MoS 3 have aroused great attention due to its special structure . As potential anode material, MoS 3 has many merits: First, it has one dimensional chain‐like structure, with more open sites to storage more Li + or Na + during the electrochemical reaction, which can provide higher specific capacity.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28] Besides layered MoS 2 , MoS 3 have aroused great attention due to its special structure. [29][30][31][32] As potential anode material, MoS 3 has many merits: First, it has one dimensional chain-like structure, [29] with more open sites to storage more Li + or Na + during the electrochemical reaction, which can provide higher specific capacity. Second, its high conductivity can improve the electron transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%